2012
DOI: 10.1111/j.1349-7006.2012.02324.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of granulocytic sarcoma in adult patients with acute myeloid leukemia

Abstract: To investigate the clinical significance of granulocytic sarcoma (GS) in adults with acute myeloid leukemia (AML), 434 consecutive patients with AML were analyzed retrospectively. Forty-five patients (10.4%) with GS at diagnosis were younger (P < 0.001), presented with higher white blood cell counts (P = 0.03) and were more likely to conform to French-American-British M4 (P = 0.001) and M5 (P = 0.045) classifications than those without GS. In contrast, no significant difference in frequency of cytogenetic abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 27 publications
1
26
0
3
Order By: Relevance
“…Furthermore, GS was associated with higher relapse rate and lower disease-free survival. 4 As several investigators have previously reported, these findings indicate that GS is one of the features of high-risk disease in adult AML. 5,6 However, the optimal therapeutic strategy for GS remains unclear, especially in regards to the indications for need of allogeneic hematopoietic stem cell transplantation (allo-HSCT).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, GS was associated with higher relapse rate and lower disease-free survival. 4 As several investigators have previously reported, these findings indicate that GS is one of the features of high-risk disease in adult AML. 5,6 However, the optimal therapeutic strategy for GS remains unclear, especially in regards to the indications for need of allogeneic hematopoietic stem cell transplantation (allo-HSCT).…”
Section: Introductionsupporting
confidence: 55%
“…GS group was significantly younger and had higher white blood cell counts compared with non-GS group as our previous report. 4 Clinical characteristics of the GS group In 44 patients with GS, the most frequently site of GS was the lymph nodes. GS occurred at two distinct sites concomitantly in six patients.…”
Section: Clinical Characteristics Of the Gs And Non-gs Groupsmentioning
confidence: 99%
“…There are four clinical presentations of myeloid sarcoma (5): i) Accompanied with acute myeloid leukemia (AML); ii) could be the portent of AML; iii) could be associated with myelodysplastic disease transforming to leukemia; and iv) solitary tumors. However, such localized primitive granulocytic sarcomas are extremely rare and they could develop to AML if no treatment is provided (5). The case in the current study presented as multiple solitary tumors and the routine bone marrow examination was normal.…”
Section: Discussionmentioning
confidence: 92%
“…It occurs in from 3-9% of patients with acute myeloid leukemia (AML) (1,2). MS usually occurs concomitantly with or after the diagnosis of AML (3)(4)(5). It may also present antedating the onset of systemic bone marrow leukemia (6,7), and many such cases are misdiagnosed as lymphoma (8).…”
Section: Introductionmentioning
confidence: 99%